SPE International Conference on Health, Safety and Environment in Oil and Gas Exploration and Production 2000
DOI: 10.2118/61468-ms
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Toxicological Characterisation of Water Accommodated Fractions Relevant for Oil Spill Situations

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe laboratory methodology and main findings from a characterisation study of Water Accommodated Fraction (WAF) from crude oil / oil products are presented.The study emphasises a tight connection between chemical and toxicological characterisation of WAF. The WAF solutions were prepared in standardised, closed, low energy systems with oil/seawater. WAF is of special interest because it has a high bioavailability to marine organisms, and is relevant both in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…With DOSS being an anionic surfactant, a possible repulsion between the polar head group while adsorbing at the oil–water interface may have accounted for the reduction in the dispersion effectiveness. Studies have shown that DOSS easily desorbs into salt water after emulsion formation, and this desorption results in the coalescence of smaller emulsion droplets into larger ones. Visual observations made during the baffled flask test attest to this fact because there was oiling-out and creaming of the emulsions formed with solubilized DOSS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With DOSS being an anionic surfactant, a possible repulsion between the polar head group while adsorbing at the oil–water interface may have accounted for the reduction in the dispersion effectiveness. Studies have shown that DOSS easily desorbs into salt water after emulsion formation, and this desorption results in the coalescence of smaller emulsion droplets into larger ones. Visual observations made during the baffled flask test attest to this fact because there was oiling-out and creaming of the emulsions formed with solubilized DOSS.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of larger emulsion droplets increases their rising velocity and as a result, these oil droplets fell out of the sampling zone during the analysis done with the baffled flask test. The oxyethylene “hairs” in Tween 80 are important for providing steric stabilization to the oil droplets and preventing their coalescence . The rate of desorption of Tween 80 from the oil–water interface has therefore been reported to be much slower than that of DOSS, and this is responsible for the much higher dispersion effectiveness recorded for Tween 80 at higher SOR.…”
Section: Resultsmentioning
confidence: 99%
“…Because dispersants often are a key oil spill response option, dispersant may be added to the test oil during WAF preparation at a volume ratio that reflects the dosage applied in field response (e.g., 1:20 dispersant to oil). The test procedure used to prepare chemically dispersed oil (chemically enhanced WAF [CEWAF])—including the oil loading selected, amount of mixing energy, mixing and settling times, and use of chemical dispersant—can greatly affect the composition of the WAFs, including the amount of oil that is entrained in the test media as oil droplets . Often, this complicates comparison of toxicity results for oils among studies with different experimental designs.…”
Section: Introductionmentioning
confidence: 99%
“…A concentration of a chemical in water resulting in a 50% decrease in the bioluminescence of the target bacterium at a certain time (5-15 min) is used as an indicator for the toxicity assessment (King et al, 2014). EC 50 values of oil WSF ranged from 1.08 to 17.18 mg/L, depending on the composition of oils (Hokstad et al, 2000;Rhoton et al, 2001;Fuller et al, 2004;Reá tegui-Zirena et al, 2014). Normally, aromatics in WSF have a much higher toxicity than saturates.…”
Section: Bacteriummentioning
confidence: 99%